One root of a quadratic equation is 3 +V2. The quadratic equation is?
(a) x2- 6x - 7 = 0.
(b) x2+ 6x - 7 = 0.
(c) x2+ 6x + 7 = 0.
(d) x2- 6x + 7 = 0.
Answers
Answered by
0
Answer:
2+6x−7=0
x2+6x+9−9−7=0
x2+3x+3x+9=+16
x(x+3)+3(x+3)=16
(x+3)(x+3)=16
(x+3) 2=±(4)2
x+3=±4
2×a×b=6x
2×x×b=6x(∵a=x)
b= 2x/6x
b=3
b 2=9
Taking square root on both the sides,
(Half of coefficient of x = 26
∴b=3)
If, x + 3 = 4 x +3 = - 4
x = 4 - 3 x = - 4 - 3
x = 1 x = - 7
∴ 1 and - 7 are the roots of x2+6x−7=0
Similar questions